(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research refers to the details and the origin of Darbandians life, and their first coming in Kirmashan region. This ethnic group perform themselves differently as they compared to their surrounding area in the fields of style and culture. They speak in Kalhurr dialect, They migrated from Nawdarwand of Kirmashan towards the west of Iran border until they arrived their in habited area which includes thirty four villages in different areas, Now, Segrdkan sub-district and its surrounding is considered as the center of Darbandians living. Meanwhile, this research highlights the factors behind the immigration and disperse of Darbandians in the second half of the century and the beginning of the century from their hometown.The main factor can be seen in the conflict between the major authorities on Iran land, the war and the chaos in border districts is another factor and the policy of persecution is another factor. The research also refers to the ways of their coming and arrival to the first settlement place where includes the villages of (Omargwmbat, Gorqaraj, kanilala, and segrdkan), then their spread to the other villages, after that referring to the major clans and the families of darbandians.